PENGARUH INTERVAL TRAINING DAN OREGON CIRCUIT TERHADAP VO2MAX DI TINJAU DARI BODY MASS INDEX (BMI) ATLET GULAT KABUPATEN KARO - Barus, Julius Boy Nesra Basgimata; Sinuraya, Janwar Frihasan (Universitas Quality, 2024)
Wrestling is a martial art that brings two people together on the mat, and the fight is carried out using the techniques of pulling, pushing, tackling, slamming, pressing, lifting and holding the opponent so that both of the opponent's shoulders stick to the mat without violating the applicable rules. Wrestling requires a strong physique because it uses muscles throughout the body; Therefore, wrestling athletes must maintain their physical condition through planned training. Therefore, in order to play optimally, each player must have excellent physical condition. Maximum oxygen volume (VO2max) is an indicator of physical condition. This study aims (1) to determine the effect of interval training on increasing VO2max; (2) to determine whether there are differences between athletes who have a normal and high body mass index regarding VO2max. This research is experimental research using quantitative methodology. Wrestling athletes from Karo Regency, North Sumatra Province were the subjects of this research. In this study the independent variables were Oregon interval and circuit training; Therapy is given for four weeks with a training frequency of twice a week. The results of the research show that (1) there is a significant influence between the interval training and Oregon circuit training methods on increasing VO2max with an F value of 15.374 and a p value <0.05, so it can be concluded that the group studied using interval training was more good when compared with the group using the Oregon circuit with a difference value obtained of 0.68. (2) There is a significant difference in influence between students who have a high BMI and a normal BMI on VO2max, with an F value of 86.487 and p < 0.05. The results obtained from data analysis of wrestling athletes who have a normal BMI with an average difference of 3.14 are higher when compared to athletes with a high BMI, namely 1.22 with a difference of 1.92. (3) With an F value of 1.419 and p > 0.05, there is no significant interaction between interval training and Oregon Circuit training techniques with BMI (high and normal) on VO2Max.